2022
DOI: 10.3390/ijerph19063184
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Thickness after 8 Weeks of Strength Training, Electromyostimulation, and Both Combined in Healthy Young Adults

Abstract: The aim of this study was to verify and compare the effects of electromyostimulation training (EMS), strength training (ST), and both combined (STEMS), through the analysis of the elbow flexors muscle thickness. Forty subjects (24.45 ± 3.53 years), were randomly divided equally in 4 groups: 3 experimental groups and 1 control group. Each experimental group was submitted to one of three interventions, either an ST protocol, an EMS protocol, or a STEMS protocol. The control group (CG) did not perform any type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…These problems lead to limited comparability of MT which can be seen in MAPE and MAE between two investigators performing sonography measurement in one participant in a cross-sectional study design. This is of crucial importance when sonography is used to determine changes in MT in pre-post comparisons (Schoenfeld et al, 2017(Schoenfeld et al, , 2019Ehsani et al, 2019) considering this study found a MAPE 4.6-8.6% between investigators for the use of sonography compared to MT percentage increases of 4.5-8% in listed studies (Athiainen et al, 2005;Watanabe et al, 2014;Schoenfeld et al, 2016;Coratella et al, 2018;Matos et al, 2022). Based on this, these values do not seem to be sufficient to describe sonography as a very precise and adequate measurement device which is requested to determine muscle morphology (Ticinesi et al, 2017).…”
Section: Critical Evaluation Of Sonography Measurement To Examine Mus...mentioning
confidence: 78%
See 2 more Smart Citations
“…These problems lead to limited comparability of MT which can be seen in MAPE and MAE between two investigators performing sonography measurement in one participant in a cross-sectional study design. This is of crucial importance when sonography is used to determine changes in MT in pre-post comparisons (Schoenfeld et al, 2017(Schoenfeld et al, , 2019Ehsani et al, 2019) considering this study found a MAPE 4.6-8.6% between investigators for the use of sonography compared to MT percentage increases of 4.5-8% in listed studies (Athiainen et al, 2005;Watanabe et al, 2014;Schoenfeld et al, 2016;Coratella et al, 2018;Matos et al, 2022). Based on this, these values do not seem to be sufficient to describe sonography as a very precise and adequate measurement device which is requested to determine muscle morphology (Ticinesi et al, 2017).…”
Section: Critical Evaluation Of Sonography Measurement To Examine Mus...mentioning
confidence: 78%
“…But, especially if the aim is to determine changes from pre-to post-test, e.g., in sarcopenia (Rustani et al, 2019), or following a training intervention (Ticinesi et al, 2017), an exact determination of possible changes in morphological parameters is requested. This is underlined by documented increases of moderate effect sizes in MCSA or MT (5.56% -8.02%, d = 0.36-0.58) (Schoenfeld et al, 2016;Amirthalingam et al, 2017;Coratella et al, 2018;Prestes et al, 2019;Matos et al, 2022) in different muscle groups. In addition, there were even higher increases of up to 17.78% (from 18.0 ± 4.7 mm to 21.1 ± 16 mm, d = 0.66) (Evangelista et al, 2019) in untrained individuals following an 8-week whole body resistance training intervention and of 13.06% (from 26.8 ± 5.9 mm to 30.3 ± 5.9 mm) with d = 0.59 (Ozaki et al, 2020) in the leg muscles of untrained individuals after a 12-week training intervention -both measured via sonography.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The ability of satellite cells to regenerate increased with the increase in muscle strength and activity of the subjects (42). In an upper-extremity study (25) of people with trained status, low intensity (60% of 10 RM). EMS combined with a strength training protocol significantly increased elbow flexor muscle thickness, showing a positive hypertrophic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most previous studies have focused on lower limbs, and the impact on the upper limb is often ignored. A recent study (25) compared the effects of strength training, EMS, and a combination of both on elbow flexor muscle morphological adaptations in trained healthy young adults. The study reported a significant improvement in this parameter after EMS combined with voluntary contraction training.…”
Section: Introductionmentioning
confidence: 99%